Trends on Leadership, Social Support, and Workplace Inclusion: A Systematic Science Mapping Study - Rr. Hawik Ervina I; Qristin Violinda; Noventia Karina P; Mochamad Fadjar Darmaputra (Jurnal Maksipreneur, 2026)
This study examines the intellectual structure and research dynamics related to leadership, workplace inclusion, and social support within organizational and management contexts using a systematic science mapping approach. Data were collected from Scopus and Web of Science databases, covering publications between 2000 and 2024. Following PRISMA screening guidelines, 80 high-quality articles were included for analysis. The findings reveal an exponential growth of publications after 2015, with significant contributions from scholars in workplace, psychology, and management. Science mapping identified five major thematic clusters: inclusive leadership, workplace equity, psychosocial well-being, family engagement, and policy development. Beyond these general trends, the results hold specific implications for families, particularly working mothers raising children with special needs, whose dual responsibilities highlight the importance of robust social support systems and inclusive policies. The study highlights gaps in cross-regional comparisons and limited integration of digital transformation into workplace inclusion research. It concludes with a future agenda emphasizing interdisciplinary collaboration and longitudinal designs to address persistent inequalities in access and leadership practices. This paper contributes by synthesizing fragmented literature and offering a holistic overview that can inform both academic research and policy development.